Racism and xenophobia (Journal of Parents and Teachers, 2025)
José Suárez offers resources for teachers and pupils in both primary and secondary education to combat racism and xenophobia in education. These resources can be used in the classroom to promote tolerance, respect for diversity, culture and equality.
Keywords: Racism, Tolerance, Xenophobia, Immigration, Multiculturalism, Integration, Diversity and Ethics.